2007
DOI: 10.1007/s10194-007-0360-4
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from placebo effects in migraine treatment

Abstract: In medical research, the placebo effect is an important methodological tool. Placebo is given to participants in clinical trials, with the intention of mimicking an experimental intervention. The "nocebo" effect, on the other hand, is the phenomenon whereby a patient who believes that a treatment will cause harm actually does experience adverse effects. The placebo effect strongly influences the way the results of clinical trials are interpreted. Placebo responses vary with the choice of study design, the choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…The lack of objective measures of migraine and the known placebo effect seen in previous pharmacological studies 20 meant that adequate blinding of both patients and headache physicians was an important element in the design of the MIST trial. Although not assessed formally, we believe blinding was achieved with the sham procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of objective measures of migraine and the known placebo effect seen in previous pharmacological studies 20 meant that adequate blinding of both patients and headache physicians was an important element in the design of the MIST trial. Although not assessed formally, we believe blinding was achieved with the sham procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In migraine trials, the placebo response is high, in terms of both efficacy and side effects. 1 Thus, a proper control group to assess the placebo effect in our study would have been appropriate, consisting of patients with placebo treatment for their trigger points. Unfortunately, as already mentioned, a true placebo treatment for TrP infiltration does not exist, since dry needling, or injection of saline, is per se an effective therapeutic approach for TrP release.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown a high placebo effect with migraine treatment (18,19). Our study had no control group to evaluate the placebo effect.…”
Section: Limitationsmentioning
confidence: 96%